Parenting Practices as Prevention of Stunting Impact in Children's Psychosocial Development - Yefta Primasari; Budi Anna Keliat (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Stunting is a condition where the occurrence of failure to thrive in young children due to chronic malnutrition so that the child is too short for his age. The prevalence of stunting in children under five in Indonesia is higher than the prevalence of stunting in the world. The impact of stunting is one of them being a developmental obstacle, which if not prevented will have an impact on the sub-optimal performance of children in school and the long-term impact can be a decrease in the quality of human resources. One of the interventions that can be done is by providing stimulation of development in parenting practices to improve children's development in accordance with the stage of age. This study aims to systematically identify the effectiveness of parenting practices in childhood development. The Systematic review method is used to search articles in electronic databases namely ProQuest, Sage Publications, and Google Scholar. The keywords used are